1998
DOI: 10.1086/515429
|View full text |Cite
|
Sign up to set email alerts
|

Protein Use and Muscle‐Fiber Changes in Free‐Ranging, Hibernating Black Bears

Abstract: Studies of the metabolic and physiological changes that bears undergo during hibernation have, for the most part, supported the paradigm that bears use only fatty tissues as a metabolic substrate during hibernation. This study was performed to document the extent of protein loss and alteration of muscle-fiber characteristics of selected muscles in black bears during winter dormancy. Muscle biopsies were removed from the gastrocnemius and biceps femoris from seven free-ranging female black bears on the Uncompah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 8 publications
11
96
1
Order By: Relevance
“…While skeletal muscle mass in ground squirrels and bats is reduced by 14 -65% during hibernation (7), no significant loss in lean body mass was observed in adult black bears during hibernation (25,29), except for 4 -10% reduction in muscle protein reported specifically for lactating females (38). Hibernating brown and black bears show a net increase in plasma protein concentration (17,27), and this is consistent with elevated protein synthesis in liver during hibernation.…”
Section: Differential Gene Expression In Hibernating Black Bearsmentioning
confidence: 76%
“…While skeletal muscle mass in ground squirrels and bats is reduced by 14 -65% during hibernation (7), no significant loss in lean body mass was observed in adult black bears during hibernation (25,29), except for 4 -10% reduction in muscle protein reported specifically for lactating females (38). Hibernating brown and black bears show a net increase in plasma protein concentration (17,27), and this is consistent with elevated protein synthesis in liver during hibernation.…”
Section: Differential Gene Expression In Hibernating Black Bearsmentioning
confidence: 76%
“…During early winter 1999 and 2000, radio-collared wild bears were located in their winter dens, anesthetized with Telazol®, and temporarily extricated from their dens [12,37]. Customized IDRs and sensing leads (model 6942; Medtronic, Inc., Minneapolis, MN) were surgically implanted in early winter using aseptic techniques.…”
Section: Data Recordersmentioning
confidence: 99%
“…Clinical applications of a reduced metabolic state typical of overwintering bears include treatment for human heart failure, stroke, myocardial infarction, and extending the duration of whole organ ischemia prior to transplantation [4]. We previously demonstrated that bears have limited loss of skeletal muscle protein and strength during winter, which has applications in preventing muscle disuse atrophy [12,23,37]. It is also advantageous to conserve cardiac muscle to maintain sufficient perfusion of all body tissues during winter and to enable a response to predatory threats.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hibernating animals, such as black bears and goldenmantled ground squirrels, develop less serious muscle atrophy than non-hibernating animals, despite their inactivity during hibernation [26,27]. A study carried out in Syrian hamsters has shown that exposure to low temperature (LT) had a short-term preventive effect on hindlimb-unloaded (HU) muscle atrophy [12].…”
Section: Introductionmentioning
confidence: 99%